2009
DOI: 10.1007/s11948-009-9175-9
|View full text |Cite
|
Sign up to set email alerts
|

The Responsible Subject in the Global Age

Abstract: The first thesis of this article is that the concept of responsibility takes on an unprecedented meaning in the twentieth century resulting from the emergence of a new dimension of the other: to be responsible comes to mean not just to account for oneself in relation to the other, but also to take the other into account, to take care of the other-what I call responsibility towards (the other). The main reason for this change consists in the emergence of global risks and the necessity, as underlined by Hans Jon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As posited by Pulcini (2009, drawing from Hans Jonas), with advancements in science and technology and phenomena of globalization, today humans can not only transform nature, but also create it, disrupting evolutionary laws and posing immense threats to the ecosystems. Yet, while rational knowledge and productive capacity develop at extreme and frantic levels, the 'emotional founded awareness' about the long-term consequences of such acts, does not mature at the same pace (Pulcini, 2010). The split between knowing and feelings hinders human's ability to perceive the size and destructive potential of impelling risks (Pulcini, 2009).…”
Section: Enabling Transformative Agency: Nurturing Emotional Awarenessmentioning
confidence: 99%
“…As posited by Pulcini (2009, drawing from Hans Jonas), with advancements in science and technology and phenomena of globalization, today humans can not only transform nature, but also create it, disrupting evolutionary laws and posing immense threats to the ecosystems. Yet, while rational knowledge and productive capacity develop at extreme and frantic levels, the 'emotional founded awareness' about the long-term consequences of such acts, does not mature at the same pace (Pulcini, 2010). The split between knowing and feelings hinders human's ability to perceive the size and destructive potential of impelling risks (Pulcini, 2009).…”
Section: Enabling Transformative Agency: Nurturing Emotional Awarenessmentioning
confidence: 99%
“…This relatively new research has found that 'a language of morality' can be a crucial part of the 'agent's discursive quiver' as they attempt to shift norms and bring about systemic change (Antadze & McGowan, 2017, p. 2). Additionally, emotions can act as motivational forces supporting beliefs and judgements guiding choices and actions (Pulcini, 2010). Still, emotions and affective sentiments (e.g.…”
Section: Agency Social Entrepreneurshipmentioning
confidence: 99%
“…As posited by Pulcini (2013, drawing from Hans Jonas), with advancements in science and technology and phenomena of globalization, today humans can not only transform nature, but also create it, disrupting evolutionary laws and posing immense threats to the ecosystems. Yet, while rational knowledge and productive capacity develop at extreme and frantic levels, the 'emotional founded awareness' about the long-term consequences of such acts, does not mature at the same pace (Pulcini, 2010). The split between knowing and feelings hinders human's ability to perceive the size and destructive potential of impelling risks (Pulcini, 2013).…”
Section: Enabling Transformative Agency: Nurturing Emotional Awarenessmentioning
confidence: 99%